Se bomo iz finančne krize res izvlekli s krčenjem javnega sektorja? - Mencinger, Jože (Delavci in delodajalci, 2012)
Public debts are not the cause, they are the consequence of financial crisis; their enhancement enabled the governments to rescue banks and to prevent economic, social and political cataclysm. Thus, with rapid decrease of public expenditures and shrinking of the public sector the crisis will only deepen. The "golden rule" which imposes "proper" fiscal policy to different economic environments, strengthens asymmetric shocks of monetary policy, and discards already limited fiscal autonomy of the EU member states.
Keywords: davčna politika; ekonomska kriza; Evropska unija; javni dolgovi; javni sektor